Strategi Membaca secara Teratur dalam Meningkatkan Keterampilan Literasi Siswa di SD Islam Ash-Shiddiiqii Surabaya - Aprilia Tri Mahalani; Muhammad Yusron Maulana El Yunusi (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2023)
The  purpose of this research is to (1) regular reading strategies in improving students’ literacy skills (2) identify the obstacles students face when regularly improving their reading skills, (3) efforts that can be made to improve regular reading in improving their reading skills. Student literacy. Data was collected through interviews, classroom observations, and document analysis a qualitative approach. The results showed that two students in the complete category had good reading skills, and one student in the incomplete category had poor reading skills. Factors that hinder reading ability are the influence of television and electronic devices, interest and motivation, and lack of parental attention. On the other hand, reading ability is supported by the habit of reading, special guidance fron teachers, and the use of available facilities. And following a reading routine, such as tracking progress and reflecting, can significantly improve students’ literacy skills.